Administration of Magnesium and its Association with Prevention of Ventricular Arrhythmias Following Cardiopulmonary Bypass in Open Heart Surgery - Karim, Md Rezaul; Ahmed, Tawfiq; Biswas, Bidyut Kumar; Moinuddin, Shahriar; Hasan, Md Kamrul; Adhikary, Asit Baran (Cardiovascular Journal, 2018)
Background: The development of cardiac arrhythmias following open- heart surgery is fairly common. Hypomagnesemia appear to be a significant element in the genesis of postoperative ventricular arrhythmias. Purpose of this study is to evaluate the effects of postoperative use of magnesium following cardiopulmonary bypass and minimize the risk of dreadful ventricular arrhythmia. Methods: Total 80 (Eighty) patients were enrolled for this study divided in 2 groups, Group A (n=40): patients who were given Magnesium Sulphate and Group B (n=40): patients who were not given Magnesium. Monitoring of the patient in ICU was done for incidence of ventricular arrhythmias. Results: From this study the incidence of postoperative ventricular arrhythmia was less in the magnesium treated group than the control group. Mean serum magnesium concentration decreased to subnormal value, immediately after surgery in both magnesium-treated and untreated groups. Conclusions: Routine intravenous magnesium administration can reduce the incidence of ventricular arrhythmias after cardiac surgery following cardiopulmonary bypass. Cardiovasc. j. 2018; 11(1): 23-30